Penerapan Manajemen Risiko UMKM Madu di Kecamatan Badas Kabupaten Kediri di Tengah Pandemi COVID19 - Santoso, Rudi; Mujayana, Marya (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
The pandemic has changed the order of the world of Business. The impact of the pandemic was also felt by MSME business actors which resulted in a decrease in income. The Association of Farmers and the Development of Livestock Honey Production is one of the affected MSMEs. In addition to decreasing income, business capital has been eroded. These MSMEs do not have risk management to anticipate every business risk that occurs. This research is a qualitative descriptive study. The emphasis in this study focuses on the analysis of the conclusion process as well as the analysis on the dynamics of the observed phenomena relationship using scientific logic. The application of risk management to honey business actors recommends four things with an emphasis on three things, namely: elimination, substitution, and administration. These three things are the most appropriate recommendations to deal with the systematic risk of a COVID-19 pandemic